THE ALLOCATION SYSTEM AND RATIONALITY MEASURES IN THE VALUATION OF MIXED-CROP AGRICULTURAL LAND - Francesca Salvo; Daniela Tavano; Giovanni Rubuano (Valori e Valutazioni)
The valuation of agricultural land is a complex task, influenced by markets characterized by low transparency and limited activity, which restrict the ability to form a sufficiently representative real estate sample. The lack of information that typifies land markets makes traditional statistical and econometric models impractical. In contrast, mathematical models based on valuation systems, such as the General Appraisal System (GAS) and the Allocation System (AR), offer an effective solution. The AR, in particular, breaks down the value of a complex property into its main components, using implicit average prices to quantify the contribution of each part to the overall price. This method, primarily used for appraising average values related to surface characteristics, is well suited for the evaluation of land with multiple types of crops. Although the valuation literature attests to its reliability as a tool for assessing agricultural land, its practical application remains relatively limited. To address this gap, the present work examines the applicability of AR to land markets through the presentation of a concrete valuation case study. The main objectives are to illustrate the process of determining the assessed value and to analyze the benefits of the optimal selection of comparable sales. This phase, conducted by applying specific measures to the appraisal sample, highlights the importance of selecting comparable properties, which can be crucial in distinguishing between heterogeneous valuation results, often difficult to interpret and justify without appropriate valuation criteria.